2021
DOI: 10.1186/s12879-021-05914-1
|View full text |Cite
|
Sign up to set email alerts
|

Patients with infective endocarditis and history of injection drug use in a Swedish referral hospital during 10 years

Abstract: Background Patients with injection drug use (IDU) have increased risk of developing infective endocarditis (IE). Previous studies have reported recurrent IE, increased duration of hospital stay, poor adherence and compliance as well as higher mortality and worse outcomes after surgery in the IDU-IE patient group. Further studies are needed to provide a basis for optimized care and prevention of readmissions in this population. This study aims to describe the clinical characteristics and outcome… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The risk was significantly lower in Black than White people and lower in Hispanic than non-Hispanic people, after propensity-score matching for other demographics, socioeconomic factors, comorbidities, and medical procedures. Since the risk of developing infective endocarditis is higher in injection drug use (IDU) patients [30] our findings are consistent with the higher prevalence of IDU in whites than in blacks or Hispanics [31].…”
Section: B Comparison Of 180-day Risk For a New Diagnosis Of Endocard...supporting
confidence: 85%
“…The risk was significantly lower in Black than White people and lower in Hispanic than non-Hispanic people, after propensity-score matching for other demographics, socioeconomic factors, comorbidities, and medical procedures. Since the risk of developing infective endocarditis is higher in injection drug use (IDU) patients [30] our findings are consistent with the higher prevalence of IDU in whites than in blacks or Hispanics [31].…”
Section: B Comparison Of 180-day Risk For a New Diagnosis Of Endocard...supporting
confidence: 85%
“…We also found that injection-associated infections were more common in summer. To our knowledge, this pattern has only been observed in 2 small studies [ 7 , 42 ]. This pattern has been observed for Staphylococcal infections generally [ 23 ], which may be due to sweating and proliferation of colonized bacteria, insect bites, or close contact for example via contact sports.…”
Section: Discussionmentioning
confidence: 80%
“…Many other infections have seasonal patterns that have informed public health responses, such as seasonal immunization campaigns and heightened hospital infection control measures in winter. Bacterial skin infections in the general population are more common in summer [ 23 ], and studies in New York in the 1990s and Stockholm between 2007 and 2018 suggest that the rate of injection-associated infections is also higher in summer [ 7 ].…”
mentioning
confidence: 99%
“…The standard 4-6-week regimen should be used in the remaining patients or when therapy with antibiotics other than penicillinase-resistant penicillins are used. 330,[739][740][741][742][743][744] When the conventional i.v. route therapy is not possible, S. aureus right-sided IE in PWID may also be treated with oral ciprofloxacin (750 mg twice a day) plus rifampin (300 mg twice a day) if the strain is susceptible to both drugs, the case is uncomplicated, and patient adherence is monitored carefully.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%